Cerebral perfusion differences in women currently with and recovered from anorexia nervosa. Issue 2 (30th May 2015) - Sheng, Min; Lu, Hanzhang; Liu, Peiying; Thomas, Binu P.; McAdams, Carrie J.
Abstract: Anorexia nervosa is a serious psychiatric disorder characterized by restricted eating, a pursuit of thinness, and altered perceptions of body shape and size. Neuroimaging in anorexia nervosa has revealed morphological and functional alterations in the brain. A better understanding of physiological changes in anorexia nervosa could provide a brain-specific health marker relevant to treatment and outcomes. In this study, we applied several advanced magnetic resonance imaging (MRI) techniques to quantify regional and global cerebral blood flow (CBF) in 25 healthy women (HC), 23 patients currently with anorexia (AN-C) and 19 patients in long-term weight recovery following anorexia (AN-WR). Specifically, CBF was measured with pseudo-continuous arterial spin labeling (pCASL) MRI and then verified by a different technique, phase contrast (PC) MRI. Venous T2 values were determined by T2 relaxation under spin tagging (TRUST) MRI, and were used to corroborate the CBF results. These novel techniques were implemented on a standard 3T MRI scanner without any exogenous tracers, and the total scan duration was less than 10 min. Voxel-wise comparison revealed that the AN-WR group showed lower CBF in bilateral temporal and frontal lobes than the AN-C group. Compared with the HC group, the AN-C group also showed higher CBF in the right temporal lobe. Whole-brain-averaged CBF was significantly decreased in the AN-WR group compared with the AN-C group, consistent with the PC-MRI results. Venous T2 values were lower in the AN-WR group than in the AN-C group, consistent with the CBF results. A review of prior work examining CBF in anorexia nervosa is included in the discussion. This study identifies several differences in the cerebral physiological alterations in anorexia nervosa, and finds specific differences relevant to the current state of the disorder. Highlights: Regional and global cerebral blood flow (CBF) is examined in anorexia nervosa with MRI techniques. We compare healthy women (HC), women currently with anorexia (AN-C), and women in weight-recovery following anorexia (AN-WR). Whole-brain CBF was less in the AN-WR group than in the AN-C group. Venous T2 relaxation values were less in the AN-WR group than in the AN-C group. Regional differences were primarily in the frontal and temporal lobes.